2010
DOI: 10.4049/jimmunol.1000952
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of Large Functionally Active CD11/CD18 Integrin Complexes from Leukocyte Membranes during Synovial Inflammation Distinguishes Three Types of Arthritis through Differential Epitope Exposure

Abstract: CD18 integrins are adhesion molecules expressed on the cell surface of leukocytes and play a central role in the molecular mechanisms supporting leukocyte migration to zones of inflammation. Recently, it was discovered that CD11a/CD18 is shed from the leukocyte surface in models of inflammation. In this study, we show that shedding of human CD11/CD18 complexes is a part of synovial inflammation in rheumatoid arthritis and spondyloarthritis but not in osteoarthritis. In vivo and in vitro data suggest that the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
55
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 75 publications
9
55
0
Order By: Relevance
“…We show that peritoneal levels of soluble integrin ␤2 are elevated both at the time of initial exiting of resident macrophages and during the slow resolution phase. As shown by studies of synovial fluids (12), the release of soluble integrin ␤2 may buffer leukocyte adhesion thus further limiting leukocyte influx and/or activation. In addition, soluble complexes may retain signaling capabilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We show that peritoneal levels of soluble integrin ␤2 are elevated both at the time of initial exiting of resident macrophages and during the slow resolution phase. As shown by studies of synovial fluids (12), the release of soluble integrin ␤2 may buffer leukocyte adhesion thus further limiting leukocyte influx and/or activation. In addition, soluble complexes may retain signaling capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…In human blister fluid, truncated ectodomains of ␣L␤2 (LFA-1) were detected, and neutrophils and monocytes showed a loss of cell surface ␣L␤2 (10). More recently, shedding of integrin ␤2 complexed with different ␣ subunits was shown to be a part of synovial inflammation in rheumatoid arthritis and spondyloarthritis but not in osteoarthritis (12). These authors further demonstrated the ability of soluble integrin ␤2 to inhibit monocytic cell adhesion to ICAM-1.…”
mentioning
confidence: 91%
“…Hybridoma cells producing monoclonal antibody KIM127, reacting with an epitope of human CD18 (43), were purchased from the American Type Culture Collection (Manassas, VA, USA), and the antibody was purified from culture supernatant as previously described (44). IgG1 from murine myeloma was used as an unspecific control antibody.…”
Section: Methodsmentioning
confidence: 99%
“…tissues, but also the shed molecules appear to act as dominantnegative inhibitors of CD11 or CD18 function on leukocytes (Gjelstrup et al, 2010).…”
Section: Mmp9 Cleaves 4 Integrinmentioning
confidence: 99%